Estresse salino e relação potássio:cálcio em berinjela fertigada - Santos, Jefferson Mateus Alves Pereira dos (Universidade Federal Rural do Semi-Árido, 2018)
The quality of fruits and vegetables is directly related to the type of water used in irrigation and the adequate supply of nutrients. Therefore, this study aimed to evaluate the effect of salinity of irrigation water in interaction with different ionic ratios between potassium and calcium via fertigation in eggplant culture. The experiment was installed in the Department of Environmental and Technological Sciences of Federal Rural Semi-Arid University (UFERSA), in Mossoró-RN. The treatments were formed by the combination of five ionic ratios between potassium and calcium (K+/Ca2+) (F1= 4,2:1; F2= 3,5:1; F3= 2,8:1; F4= 2,2:1; F5= 1,8:1), with four levels of salinity in irrigation water (S1- 0,5; S2- 2,0; S3- 3,5; e S4- 5,0 dS m-1). The experimental design was in randomized blocks, in a 5 x 4 factorial scheme, with four replications. The responses of the plants to the treatments used were evaluated through growth analyzes (plant height, stem diameter, number of leaves, leaf area, stem dry mass, leaves, fruits total and chlorophyll content), production parameters (fruit length and diameter, number of fruits per plant, average mass and yield), quality of fruits (total acidity, ° Brix, firmness, pH and vitamin C) and nutritional analysis (Nitrogen, Phosphorus, Potassium, Calcium and Magnesium in the stem, leaves and fruits). The salinity of the irrigation water reduced the production variables, biomass accumulation and relative index of chlorophyll, regardless of the K+/Ca2+ ratio used. The F4 fertigation promoted the maintenance of plant height when submitted to the highest salinities. F1 fertigation provided an increase in vitamin C with increased salinity and fertiations with higher calcium concentrations (F4 and F5) promoted higher SS/AT ratios and pulp firmness. F5 fertigation resulted in increase of P in fruits and total accumulation; the fertility F4 and F5 increased the K content in the fruits and the F3 and F4 fertilizations increased the Ca values in the fruits and in the total accumulated in the eggplant
Keywords: Solanum melongena; Cultivo de hortaliças; Manejo da fertigação; Estresse salino; Solanum melongena; Cultivation of vegetables; Fertigation management; Saline stress; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO